The Impact of Inflation, Exchange Rate, Interest Rate, and Economic Growth on The Indonesia Stock Exchange Composite Index - Abdullah Fauzi; Amin Wijoyo (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study aims to analyze the influence of macroeconomic variables specifically inflation, exchange rate, interest rate, and economic growth on the Composite Stock Price Index (IHSG) in Indonesia during the 2005–2023 period. Recent fluctuations in global and domestic economic conditions have raised concerns about how these key indicators affect stock market performance, prompting the need for empirical examination. The research objective is to identify which of these variables significantly affect the IHSG and to confirm whether common assumptions about their influence hold true over a longer time frame. A saturated sampling method was employed, yielding 19 annual time-series data points. The data were analyzed using multiple linear regression techniques with the assistance of EViews 12 software. The findings reveal that the exchange rate and economic growth both have a significant negative impact on IHSG, whereas the interest rate exerts a significant positive influence. In contrast, inflation does not significantly affect the index. These results suggest that investors, market analysts, and policymakers should closely monitor changes in exchange rates, interest rates, and economic growth, as these factors can meaningfully impact market dynamics. The conclusion drawn from this study confirms that not all macroeconomic variables influence IHSG as commonly assumed, and further research may be necessary to explore these relationships in different economic contexts or with higher-frequency data.